A diagnostic algorithm to identify paired tumors with clonal origin. Issue 11 (2nd September 2013) - Nemes, Szilárd; Danielsson, Anna; Parris, Toshima Z.; Jonasson, Junmei Miao; Bülow, Erik; Karlsson, Per; Steineck, Gunnar; Helou, Khalil
<x xml:space="preserve">Abstract</x> Despite practical implications we still lack standardized methods for clonality testing of tumor pairs. Each tumor is characterized by a set of chromosomal abnormalities, nonrandom changes preferentially involving specific chromosomes and chromosomal regions. Although tumors accumulate chromosomal abnormalities during their development, the majority of these alterations is specific and characteristic for each individual tumor is not exhibited at the population level. Assumingly, secondary tumors that develop from disseminated cells from the primary tumor inherit not only chromosomal changes specific for the cancerous process but also random chromosomal changes that accumulate during tumor development. Based on this assumption, we adopted an intuitive index for genomic similarities of paired tumors, which ranges between zero (completely different genomic profiles) and one (identical genomic profiles). To test the assumption that two tumors have clonal origins if they share a higher degree of genomic similarity than two randomly paired tumors, we built a permutation‐based null‐hypothesis procedure. The procedure is demonstrated using two publicly available data sets. The article highlights the complexities of clonality testing and aims to offer an easy to follow blueprint that will allow researchers to test genomic similarities of paired tumors, with the proposed index or any other index that fits their need. © 2013 Wiley Periodicals, Inc.